Comparative Study of the Themes of Ferdowsi’s Shahnameh in Old and Contemporary Iranian Miniatures - Pourmokhtar, Sediqeh; Afshari, Morteza (Journal of History Culture and Art Research, 2018)
One of the main sources of Persian painting is literary works. Epic literature, and especially the Shahnameh of Ferdowsi, has been noticed more than other literary types because it narrates the chivalry of the kings and national heroes of Iran as well as the Iranian people. In different periods, the Iranian artists benefit the themes of this valuable book; one of the main pillars of Iranian literature. But the encounter of artists to this work varied in different periods. This study examines this encounter. By conducting a case study, this research inspects old Iranian miniatures of Tahmasbi Shahnameh and their adaptation in terms of contents and literary themes with works of contemporary Iranian artists, namely Hossein Behzad, Majid Mehregan, Ardeshir Mojarad Takestani, Mohammad Baqer Aghamiri, and Mahmoud Farshchian. The research has been carried out through descriptive-analytical and comparative approach. The main purpose of this study is finding out how the old and contemporary Iranian painting encounter with the themes of Ferdowsi’s Shahnameh as the main basis of Iranian epic literature. Therefore, the present study seeks to answer this question; what are the differences and similarities between the old and contemporary miniatures regarding epic Iranian literature? And what are the causes of these differences and similarities? The findings of this research show that similarities and differences are a function of social and economic conditions and also changing the artist and audiences place.